Pembuatan Logo UMKM Taso Ndeso Dan Limunite Di Kelurahan Sukorejo Kota Blitar - Nico Akbar Priyambudi; Bowo Santoso (Jurnal Masyarakat Mengabdi Nusantara, 2023)
A logo is a tool for communicating to potential customers in order to convey the character, values, and important aspects of a company or business. It serves not only as a company's identity but also as a visual representation that ideally captures the overall essence of the organization. It is important to understand the theory behind logo design and the philosophy behind each element within the logo in order to effectively achieve the goals of the logo. The creation of logos for UMKM Taso Ndeso and Limunite is expected to enhance branding efforts, making them more widely recognized by the public and ultimately increasing sales.